Saudi English for specific purpose students’ attitudes toward the learning of English language: An investigative study - Alharbi, Bader (Frontiers in Education, 2022)
Students' attitudes are usually consulted before launching any learning/teaching program since they are the center of the learning process. This study is also motivated by such an aim as it gauges the attitudes of Saudi health track students on learning English for Specific Purpose (ESP). It also explores the factors that impact the students in their endeavors. The study applies mixed methods by conducting a survey and follow-up interviews to gather information from 57 Saudi students enrolled at the Preparatory Year Program, and interviews with 25 students. Findings show that the students have a moderately positive attitude towards learning English. Further, students’ responses aggregate towards moderate attitudes toward learning the target culture. In addition to that, the study reports some factors which shape the students' positive attitudes towards learning English: (1) teaching quality, (2) classroom scenario, (3) classroom environment. The study indicates the necessity of engaging students in a relaxed learning environment. As far as the EFL teachers are concerned, they need to take into consideration their students' interests while preparing and delivering the lectures.